Challenges and opportunities facing beekeepers on commercializing bees products in Tanzania: The evidence of Mvomero District, Morogoro - Munuo, Dorice Dengenesa (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of the degree of Master's of Business Administration in Corporate Management (MBA-CM) of Mzumbe University.